PdMo nanoflowers for endogenous/exogenous-stimulated nanocatalytic therapy - Liang, Xinqiang; Tang, Yanping; Kurboniyon, Mekhrdod S.; Luo, Danni; Tu, Guiwan; Xia, Pengle; Ning, Shufang; Zhang, Litu; Wang, Chen (Frontiers in Pharmacology, 2023)
The clinical application of reactive oxygen species (ROS)-mediated tumor treatment has been critically limited by inefficient ROS generation. Herein, we rationally synthesized and constructed the three-dimensional PdMo nanoflowers through a one-pot solvothermal reduction method for elaborately regulated peroxidase-like enzymatic activity and glutathione peroxidase-like enzymatic activity, to promote oxidation ROS evolvement and antioxidation glutathione depletion for achieving intensive ROS-mediated tumor therapy. The three-dimensional superstructure composed of two-dimensional nanosheet subunits can solve the issues by avoiding the appearance of tightly stacked crystalline nanostructures. Significantly, Mo is chosen as a second metal to alloy with Pd because of its more chemical valence and negative ionization energy than Pd for improved electron transfer efficiencies and enhanced enzyme-like activities. In addition, the photothermal effect generated by PdMo nanoflowers could also enhance its enzymatic activities. Thus, this work provides a promising paradigm for achieving highly ROS-mediated tumor therapeutic efficacy by regulating the multienzymatic activities of Pd-based nanoalloys.